2022
DOI: 10.1111/ffe.13845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser‐scan strategy on microstructure and fatigue properties of 316L additively manufactured stainless steel

Abstract: The particular roles of grain morphology and defects, controlled using laser‐scan strategies, on the mechanical properties and the fatigue behavior of 316L stainless steel are investigated. Microstructural characterization and X‐ray tomography analysis was performed to understand the genesis of polycrystalline microstructure and defects. Tensile and fatigue tests were performed to analyze the effect of defect population and microstructural properties on plasticity and damage mechanisms during monotonic and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…With the other process parameters determined, the effect of the scanning strategy on the fatigue performance is equally non‐negligible. Roirand et al 90 studied the fatigue performance of SLM 316L SS produced by three scanning strategies and indicated that no‐rotation strategy introduced anisotropy in the plastic behavior, rotation between layers strategy increased the density of porosity defects, and the chessboard strategy formed LoF defects, resulting in the lowest fatigue performance. Wan et al 91 discovered that the no‐rotation strategy resulted in SLM Inconel 718 materials with finer grains compared to the 90°‐rotation strategy, which, in turn, resulted in better fatigue properties.…”
Section: Fatigue Characteristics Of Am Metalsmentioning
confidence: 99%
“…With the other process parameters determined, the effect of the scanning strategy on the fatigue performance is equally non‐negligible. Roirand et al 90 studied the fatigue performance of SLM 316L SS produced by three scanning strategies and indicated that no‐rotation strategy introduced anisotropy in the plastic behavior, rotation between layers strategy increased the density of porosity defects, and the chessboard strategy formed LoF defects, resulting in the lowest fatigue performance. Wan et al 91 discovered that the no‐rotation strategy resulted in SLM Inconel 718 materials with finer grains compared to the 90°‐rotation strategy, which, in turn, resulted in better fatigue properties.…”
Section: Fatigue Characteristics Of Am Metalsmentioning
confidence: 99%
“…In recent years, extensive research has been carried out to study the anisotropic behavior of LPBF-fabricated metallic components. [14][15][16][17] Hugo et al 18 investigated the effect of laser scanning strategies on grain morphology and defects in 316L and shown that scanning strategies determine anisotropy in the plane vertical to the build direction. Sun et al 19 found that the build direction had a slight effect on the tensile strength and elongation but a significant effect on the fatigue properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Roirand et al 18 mentioned the effort that laser powder-bed fusion users are making nowadays to optimize the laser-scan strategies to reduce residual stresses, minimize the occurrence of defects, and tailor resulting local microstructures and, consequently, their effect on the static and fatigue mechanical behavior. From the printing strategies used during this investigation (Section 2.2), the chessboard is one of the most widely used in industrial applications since it is one of the best at mitigating residual stresses, especially for large components, and can reduce anisotropic plastic behavior with an island strategy.…”
Section: Introductionmentioning
confidence: 99%
“…From the printing strategies used during this investigation (Section 2.2), the chessboard is one of the most widely used in industrial applications since it is one of the best at mitigating residual stresses, especially for large components, and can reduce anisotropic plastic behavior with an island strategy. 18 Nevertheless, rotation between layers results in lower resting times and increased gas pores. Therefore, the choice of laser scanning for industrial applications should be made cautiously and in an informed manner, which justifies the present research.…”
Section: Introductionmentioning
confidence: 99%